Generative Artificial Intelligence with a Human Touch: Building HANA - Conrad A. Johnson (Washington University Journal of Law and Policy, 2026)
This Essay examines how generative artificial intelligence (GenAI) can be integrated into legal education and public interest law practice in a way that meaningfully enhances—rather than diminishes—human judgment, professional responsibility, and access to justice. Drawing on the experience of Columbia Law School’s Lawyering in the Digital Age Clinic, the Essay situates GenAI within an experiential pedagogy that emphasizes competence, ethical awareness, and collaborative problem-solving. It argues that law students and lawyers must move beyond a passive or uncritical use of GenAI tools; toward a deeper understanding of how these systems operate, the risks they pose, and the opportunities they present for improving legal services when thoughtfully designed and implemented. By illustration, the Essay offers a detailed case study of HANA—the Housing Access Navigator Assistant—a custom, closed GenAI tool developed by the Clinic in close partnership with The Legal Aid Society to support its Housing Justice Helpline. Designed around three core principles—maintaining a human touch, ensuring expert oversight, and protecting data privacy—HANA demonstrates how GenAI can be deployed to support frontline legal advocates rather than replace them. By streamlining complex legal analysis, facilitating supervisor consultation, and generating accurate, multilingual follow-up communications, HANA reduced call times while assisting advocates in providing enhanced, customized service to tenants facing eviction. Finally, the Essay distills lessons learned from both the educational and practice-based dimensions of the project. It contends that teaching GenAI through supervised, real-world experience is a particularly potent way of preparing students for contemporary law practice and meeting lawyers’ ethical obligations. At the same time, it offers practical guidance for legal organizations seeking to integrate GenAI responsibly; emphasizing iterative design, human oversight, cross-disciplinary collaboration, and scalability. Together, these insights suggest a model for leveraging GenAI as a tool for educational and institutional capacity-building while expanding access to justice—one that keeps lawyers firmly in the loop at a pivotal moment for legal education and the profession.
Keywords: #GenAILegalEd; #ClinicalLegalEducation; #ResponsibleAI; #LegalEthicsAndAI; #LegalAidInnovation; #AIForTenants